2016
DOI: 10.1016/j.jaci.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Defects of B-cell terminal differentiation in patients with type-1 Kabuki syndrome

Abstract: Background Kabuki syndrome (KS) is a complex multi-system developmental disorder associated with mutation of genes encoding histone-modifying proteins. In addition to craniofacial, intellectual, and cardiac defects, KS is also characterized by humoral immune deficiency and autoimmune disease, yet no detailed molecular characterization of the KS-associated immune phenotype has previously been reported. Objective To characterize the humoral immune defects found in KS patients with KMT2D mutations. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 54 publications
5
78
0
2
Order By: Relevance
“…Instead, he might have benefitted from the concomitant CGD regarding the elevated Ig production. Additionally, KS causes reduced rates of somatic hypermutation of IgG and deficiency of IgA in nearly all patients due to the dysregulation in the B-cell terminal differentiation pathway (11). Our patient had increased IgA and IgG level and this was concordant with CGD.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Instead, he might have benefitted from the concomitant CGD regarding the elevated Ig production. Additionally, KS causes reduced rates of somatic hypermutation of IgG and deficiency of IgA in nearly all patients due to the dysregulation in the B-cell terminal differentiation pathway (11). Our patient had increased IgA and IgG level and this was concordant with CGD.…”
Section: Discussionsupporting
confidence: 58%
“…Another question from this case is as follows: Did molecular upregulation due to KS play a role in the late presentation of CGD? KS is associated with a modest immunological defect in antibody formation, which may culminate in a common variable immunodeficiency like presentation (9,11). Many KS patients show increased susceptibility to infections and have reduced immunoglobulin serum levels due to the defect in the B-cell pathway (11), while some patients may suffer from autoimmune manifestations, such as autoimmune thyroiditis, idiopathic thrombocytopenia or hemolytic anemia (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…7). Nevertheless, the CSR defects that we and others (Ortega-Molina et al 2015) observed with MLL3/MLL4 deficiencies in mice remain to be elucidated and may help to model the immune defects observed in human Kabuki syndrome that harbor mutations in Mll4 (Lindsley et al 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Defects in histone and chromatin modification enzymes have been described in patients with Kabuki syndrome, a complex multisystem syndrome that includes hypogammaglobulinemia, reduced naïve and switched memory B cells, and an increase in the CD21 low B-cell population, all of which are often found in patients with CVID. In Kabuki syndrome, the B-cell differentiation defect was shown to be associated with an impaired histone modification process, which is fundamental for correct B-cell development [28].…”
Section: Ptenmentioning
confidence: 99%